Cardiac autonomic neuropathy is associated with ectopic fat distribution in autoimmune but not in type 2 diabetes - Renata Risi; Rocco Amendolara; Angelo Lauria Pantano; Valeria Fassino; Luca D’Onofrio; Lucia Coraggio; Daniela Luverà; Davide Masi; Mikiko Watanabe; Lucio Gnessi; Raffaella Buzzetti; Ernesto Maddaloni (Cardiovascular Diabetology)
Abstract Background Cardiac autonomic neuropathy (CAN) is a life-threatening complication of diabetes. While obesity is a well-known risk factor of dysautonomia, the association between CAN and body fat distribution has not been fully clarified, especially in autoimmune diabetes (AD). Aim To evaluate if the association between CAN and body fat distribution differs between AD and type 2 diabetes (T2D). Methods Body fat distribution was evaluated by Dual X-Ray Absorptiometry in 143 people with diabetes (44 with ADand 99 with T2D) undergoing clinical screening for CAN. The association of CAN with markers of ectopic fat distribution was evaluated in multivariate regression models adjusting for confounders and testing for the interaction between diabetes type and CAN. Results A significant interaction between CAN and diabetes type was found with respect to markers of ectopic fat distribution. Specifically, people with CAN had significantly higher amount of visceral adipose tissue (530 [376–665]g versus 251[189–360]g, p = 0.001), total fat mass (22708[20200–27845]g versus 15434[12981–21879]g, p = 0,016), and trunk-to-leg ratio (0.88 [0.75–1.04] versus 0.70 [0.56–0.78], p = 0,023) compared to those without CAN only in participants with AD, but not in T2D (p-values for interaction < 0.05 for all comparisons). Conclusion Ectopic fat distribution is more strongly associated with CAN in AD than in T2D. This highlights the distinct role of fat distribution in the cardiometabolic health of people with AD, suggesting the need for further studies to better understand the pathophysiology and implications of overweight in this population.